Molecular Regulation of Cell Wall Structure During Wood Formation in Forest Trees - Lei Yue; Xin Wei; Xia An; Shuangshuang Liu; Xing Liu; Jinghui Gao; Jiali Zhao; Renan Lin; Jinwang Wang; Huizi Liu (Journal of Natural Fibers)
There is a growing demand for wood as a sustainable energy source and an essential carbon sink for ecosystems. Wood formation is a dynamic process involving plant radial growth in various stages, including vascular cambial cell proliferation, xylem mother cell differentiation and expansion, secondary cell wall thickening, and programmed cell death. Wood formation is controlled by highly complex molecular regulatory networks. Identifying and analyzing the molecular mechanisms regulating key target genes is crucial for further characterizing how wood is formed. This article summarizes the current knowledge regarding wood formation and the underlying molecular regulatory mechanisms.